AKSI CEGAH STUNTING MELALUI PROGRAM KELUARGA BINAAN DI DESA DARSONO KECAMATAN ARJASA - yahya, Ahmad Amir; anggraeni, Ernawati; Septiana, Alifia Fatin; Hendrawan, Aliffia Widya Putri; Nadirawati, Arzeti Bilbina; Salsabila, Firdha Yuniarta; Ningsih, Fitria; Indriani, Hilmalia; Amiq, Muhammad Fakhrial; Rosyidin, Rahmat Fatih; Annisa, Rofiu Sisil; Dewi, Santi Ana; Jannah, Shobrina Noratul; Faqiha, Yuki Annisa Zainun (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
This research aims to reduce the prevalence of stunting in Darsono Village by addressing environmental factors and ensuring proper nutrition for toddlers. Through Collaborative Community Service (KKN)163 Team program, education on nutrition fulfillment and a demonstration of innovative food were conducted. The research methodology encompassed planning, preparation, implementation, and evaluation. Three selected families were monitored for 33 days, involving measurements of weight and height, along with nutritional interventions. The results indicated an improvement in the nutritional status of the three toddlers. This program successfully increased the awareness of mothers regarding the significance of nutrition fulfillment and healthy food innovation. The outcomes of the visits and interventions displayed an enhancement in the weight and height of the toddlers, showcasing the success of the program. The research underscores the importance of education and interventions in addressing stunting. The recommendation is to continue similar programs, involve more stakeholders, and expand the coverage to other areas to tackle the issue of stunting on a broader scale. Hence, such initiatives can contribute to combating stunting and enhancing the well-being of future generations